(untitled) (Contemporary Journal of Social Science Review, 2025)
This study explored psychological resilience and professional identity among visually impaired educators in Pakistan. Visually impaired educators often face social, institutional, and professional challenges while performing their academic responsibilities in schools, colleges, and universities. Despite these barriers, many educators demonstrated resilience, adaptability, and strong professional commitment within educational settings. The study adopted a qualitative research approach using a phenomenological research design to investigate the lived experiences of visually impaired educators regarding resilience, self-efficacy, workplace inclusion, and professional growth. Data were collected through semi-structured interviews with 15 visually impaired educators working in different educational institutions across Pakistan. The collected data were analyzed through thematic analysis to identify themes related to professional identity, discrimination, accessibility, institutional support, and career sustainability. The findings revealed that psychological resilience, supportive workplace environments, accessibility accommodations, and self-determination significantly contributed to educators’ professional confidence and long-term career sustainability. However, participants also experienced barriers related to inaccessible infrastructure, social stigma, and limited institutional support. The study contributes to disability studies and inclusive education literature by highlighting the professional experiences of visually impaired educators and emphasizing the importance of inclusive educational policies and equitable workplace practices in Pakistan.